Beliefs of the International University Students towards Performing English Oral Presentation in Academic Settings. “Pilot study” - Benraghda, Abdelmadjid; Zuraina, Ali; Noor Raha, Mohd Radzuan (ESP World, 2017)
The current study addresses the issue of international students’ beliefs towards oral presentation in English language in academic settings. The purpose of this research is to find out about their beliefs on speaking and delivering oral presentation in English language as foreign language. The participants were 30 male and female international students. A survey was used in this study that was adapted from Beliefs About Language Learning Inventory (BALLI) and demographic background questionnaire. The results showed that the international university students held certain beliefs which would be detrimental to their speaking and performing oral presentation in English language.